Morphological evaluation of the effects of exercise on high-fat-diet-induced liver damage in rats - Açıkel Elmas, Merve; Atay, Nilsu; Bingöl Özakpınar, Özlem; Arbak, Serap; Kolgazi, Meltem; Şener, Göksel; Ercan, Feriha (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study was aimed to investigate the protective effects of swimming exercise on nonalcoholic fatty liver disease (NAFLD) associated with high fat diet-induced obesity, using microscopical and biochemical parameters. Materials and Methods: Sprague Dawley male rats were fed either standard chow (STD group; 6% fat) or high-fat diet (HFD group; 45% fat) for 18 weeks. Animals were divided into four groups, STD, STD + EXC, HFD, HFD + EXC. Exercise groups were submitted to swimming training 5 days of week and 1h of per day, during the last 6 weeks of the experiment. At the end of the experiment, liver samples were evaluated for morphologically and ultrastructurally. Moreover, malondialdehyde (MDA) and glutathione (GSH) levels were evaluated in liver samples. Results: Normal morphology of liver parancyma with hepatocytes and sinusoids was observed in the STD and STD+EXC groups. Steatosis, lipid accumulation, ballooned hepatocytes, decrease of glycogen deposits and fibrosis in periportal area were observed in HFD group. Liver MDA level was increased and GSH level was decreased in HFD group. Exercise treatment ameliorated these morphological and oxidative changes in HFD induced liver damage. Conclusion: Based on morphological and biochemical analysis, we could conclude that swimming training ameliorated obesity-induced liver damage by regulating lipid accumulation and oxidative damage.